NET burden in left atrial blood is associated with biomarkers of thrombosis and cardiac injury in patients with enlarged left atria - Martinod, Kimberly; Claessen, Annika; Martens, Caroline; Krauel, Krystin; Velásquez Pereira, Leydi Carolina; Witsch, Jens; Witsch, Thilo (Clinical research in cardiology, 2025)
Emerging data suggest an association between left atrial (LA) enlargement, thrombus formation, and ischemic stroke. However, it is unknown what may mediate such clot formation in LA dysfunction. Neutrophils promote large vessel occlusion and microthrombosis via neutrophil extracellular trap (NET) release, thus lying at the interface of inflammation, thrombosis, and fibrosis. - APPROACH: We conducted a prospective all-comers cohort study in patients undergoing catheterization procedures with atrial transseptal access (MitraClip, MC; left atrial appendage closure, LAAC; pulmonary vein ablation, PVA; patent foramen ovale closure, PFO). We measured NETs, cytokines, thrombotic factors, and cardiac injury markers in paired blood samples collected from peripheral blood and within the left atrium. We correlated these biomarkers with echocardiographic measures of LA structure and function (including left atrial volume index, LAVI). Data were analyzed by procedure type, and stratified by LAVI or atrial fibrillation (AF) status. - RESULTS: We enrolled 70 patients (mean age 64 years, 53% women). NETs, but not other markers, were elevated in LA compared to peripheral blood samples. Most thrombotic, inflammatory, and cardiac damage markers were elevated in LAs from MC or LAAC compared to PFO patients. Overall, NET biomarkers positively correlated with VWF, LAVI, and markers of cardiac injury and negatively with ADAMTS13 activity. LA enlargement and the presence of AF similarly stratified patients based on thromboinflammation measurements, but this was not limited to AF at the time of sample collection. - CONCLUSION: Elevated NETs and VWF in patients with enlarged LA or AF suggest enhanced thromboinflammation within the LA.